The Support for New Mums Project: A protocol for a pilot randomized controlled trial designed to test a postnatal psychoeducation smartphone application. (21st March 2019) - Fealy, Shanna; Chan, Sally; Wynne, Olivia; Dowse, Eileen; Ebert, Lyn; Ho, Roger; Zhang, Melvyn W. B.; Jones, Donovan
Abstract: Aim: To report a pilot trial protocol for testing the effectiveness of the Support for New Mums smartphone application in a cohort of first‐time mothers. Design: A pilot/feasibility randomized controlled trial using a two‐group pre‐test and repeated post‐test design. Method: This protocol follows the Standard Protocol Items: Recommendations for Intervention Trials (SPIRIT) guidelines. The Intervention group will receive access to the smartphone application for 6 weeks post birth. Both Intervention and control groups will receive standardized institutional postnatal care services. Trial funding was gained from respective grant sponsors in May and November 2016. Discussion: The Support for New Mums smartphone application could be a novel method for addressing the gap in provision of postpartum care services providing psychoeducation and improving maternal parental self‐efficacy for Australian childbearing women. Trial registration: Australian New Zealand Clinical Trials Registry ACTRN12618001580268. Abstract : 目的: 报告一项试验方案, 以测试新手妈妈中"新手妈妈支持"智能手机应用的有效性。 设计: 试点/可行性随机对照试验, 采用两组(预测和重复后测)设计。 方法: 该方案遵循《规范临床研究方案内容——干预试验建议》指南。干预组将在生产后6周内接触智能手机应用。干预组和对照组都将获得标准化的机构产后护理服务。2016年5月和11月, 从各自的赞助方获得了试验资金。 讨论: "新手妈妈支持"智能手机应用可能是解决产后护理服务缺口的新方法, 为澳大利亚育龄妇女提供心理教育, 提高做母亲的自我效能感。 试验注册: 澳大利亚新西兰临床试验注册中心ACTRN12618 001580268.